The impact of workplace quality on job satisfaction among the employees in Jabatan Pembangunan Persekutuan Negeri Kelantan / Farhanah Hassan - Hassan, Farhanah (2013)
Identifying the impact of workplace quality on Job Satisfaction among the Employees is the main focus in this study. There are three main objectives in this research which are to analyze demographic information of communities usage in JPPK`s workplace, ii. To find the best predictive logistic regression model for the impact of workplace quality on job satisfaction and to develop logistic regression for the impact of workplace quality on job satisfaction. A survey was conducted on employees who are currently worked in Jabatan Pembangunan Persekutuan Negeri Kelantan (JPPK). Data was collected by using self administered questionnaire. The data that had been collected was analyzed using descriptive analysis, chi-square test and binary logistic regression. 86 employees had been answered the questionnaire to represent the sample. The result had been analyzed by using Statistical Package for Social Science (SPSS) version 20. The objectives of the study are achieved. This study had been successful conducted and the researcher had come out with the conclusion and the recommendations. The recommendations can be used by Jabatan Pembangunan Persekutuan Negeri Kelantan (JPPK) to increase the Employee`s Productivity.